Evaluation of the quality of acute pain management in a pediatric surgical setting: Validation of a parent proxy modified version of the revised American Pain Society Patient Outcome Questionnaire - Chaw, Sook Hui; Lo, Yoke Lin; Shariffuddin, Ina Ismiarti; Wong, Jia Wing; Lee, Jia Yin; Leong, David Wei Jie; Ng, Kevin Wei Shan; Chan, Lucy (Wiley, 2018)
Background: Effective pain management involves a cycle of continual pain assessment, good pain control strategies, and assessment of a standard quality improvement measures. A validated questionnaire that focuses on the quality of postoperative pain management in pediatric surgical patients and parental satisfaction on pain treatment is lacking. We, therefore, modified the revised American Pain Society Patient Outcome Questionnaire to evaluate the quality of postoperative pain management in a pediatric surgical setting. The primary aim of this study was to validate the modified version of revised American Pain Society Patient Outcome Questionnaire. Methods: Parents whose children aged below 12 years and were scheduled for elective surgery in a teaching hospital, were approached to participate in this survey. The reliability of the modified version of revised American Pain Society Patient Outcome Questionnaire was evaluated using Cronbach's alpha test, while the construct validity was assessed with a principal component analysis using a varimax rotation. The parental satisfaction with pain treatment received was measured. Results: A total of 108 parents completed the questionnaire. The internal consistency of the questionnaire shows a Cronbach's alpha of 0.798. Principal component analysis revealed a four-factor structure of the 12 items which explained 69.7% of the total variance. The factors are “Interference of sleep and activity,” “Pain severity and drowsiness,” “Perception of care,” and “Adverse effects,” respectively. Our study showed that this questionnaire is a valid and reliable measure for “Interference of sleep and activity” and “Pain severity and drowsiness” factors, but not for “Perception of care” and “Adverse effects.” The results for “Perception of care” and “Adverse effects,” therefore, should be reported as individual items instead of total score. The parental satisfaction with pain treatment given was good (median 8.0; IQR 3.0). Conclusion: The modified version of revised American Pain Society Patient Outcome Questionnaire is a feasible and easy instrument to administer. The questionnaire can be used to obtain feedback from parents about the outcomes and experiences of pain management and is helpful in continuous quality evaluation and improvement in the postoperative care in a pediatric setting.